Kajian Yuridis Terhadap Sanksi Tindak Pidana Perjudian Sabung Ayam di Indonesia - Ni Luh Gede Novianti; I Nyoman Gede Sugiartha; I Gusti Agung Ayu Gita Pritayanti Dinar (Jurnal Interpretasi Hukum, 2022)
Gambling is one of the oldest games in the world, along with the development of gambling times, and is increasingly developing, one of which is the gambling of cockfighting in Balinese called â€œTakenâ€ (spurs). In Bali there is a ritual of cockfighting to harmonize human relations with Bhuana Agung called Tabuh Rah but it is often misused by some irresponsible individuals, therefore research willes to examine this. This study aims to explain the arrangements and criminal sanctions on the perpetrators of criminal acts of cockout gamblers in Indonesia. This study uses normative legal research methods with approaches to the legislation and conceptual approach. The results of the study show that the arrangement of gambling criminal acts according to the Criminal Code in Article 303 and there is also in Article 1 of the law regulated in Law Number 7 of 1974, then criminal sanctions on criminal acts of criminal acts of cockfighting gamblers can be sentenced to prison forever Years or a fine of â€“ a lot of 25 million rupiah according to Article 2 paragraph (1) of Law / 7/1974 and regulated also on the Criminal Code in Article 303.